2012
DOI: 10.21236/ada563525
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medical Metered Dose Inhalers for Functionality Testing of Bioaerosol Detection and Identification Systems

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. DisclaimerThe findings in this report are not to be construed as an official Department of the Army position unless so designated by other authorizing documents. REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
1
1
Order By: Relevance
“…Previous studies 39,40 showed much narrower aerosol particle size distributions for pMDIs containing 5 µm polystyrene particles than the pMDI in this study that contained 4.99 µm monodisperse salbutamol sulphate particles. Then a smaller GSD might have been achieved in this study, if the formulation would have been optimised further in terms of surfactant type, valve size and the volume of spacer.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies 39,40 showed much narrower aerosol particle size distributions for pMDIs containing 5 µm polystyrene particles than the pMDI in this study that contained 4.99 µm monodisperse salbutamol sulphate particles. Then a smaller GSD might have been achieved in this study, if the formulation would have been optimised further in terms of surfactant type, valve size and the volume of spacer.…”
Section: Discussioncontrasting
confidence: 47%
“…A drawback to using a sampler that requires a liquid medium is that drawing air into a liquid for prolonged periods of time can cause evaporative loss of the sample medium (Kesavan et al, 2010). A reduction in the level of sample medium has been shown to reduce the efficiency of the sample unit, in particular with the SKC Liquid impinger units.…”
mentioning
confidence: 99%